Feasibility of an enteroclysis pump for post-mortem computed tomography angiography (PMCTA). (March 2020) - Vester, M.E.M.; Servaas, E.; Beenen, L.F.M.; Clerkx, M.; de la Rie, A.; Lobé, N.H.J.; Vogel, M.J.A.; van Rijn, R.R.; Oostra, R.J.
Highlights: PMCT angiography (PMCTA) by enteroclysis pump proves to be feasible. PMCTA with readily available materials is a low-cost option for anatomy education. The use of an enteroclysis pump for PMCTA takes an additional 15–20 min. Abstract: Objective: Post-mortem computed tomography (PMCT) is an established method for disease, complications, and cause of death determination in both clinical and forensic cases. By adding intravascular infusion of contrast medium, computed tomography angiography (PMCTA) provides additional information on vascular structures and hemorrhages. When easily applicable and low in costs, this technique would be more frequently applied and of additional value to clinical and educational purposes, particularly in forensic scientific context. Materials and Methods: PMCTA was performed on 10 bodies of the anatomy department. First, a metal T-piece was inserted into the femoral artery as part of standard practice for conservation. Secondly, surplus contrast medium with sodium chloride was infused into the body through a catheter tube set attached to the metal T-piece, using a readily available enteroclysis pump from our radiology department. Results: With added costs of approximately € 266 (personnel and materials) and an additional procedure time of 15–20 min, successful infusion of contrast mixture was achieved with the enteroclysis pump. Partial or complete opacification was measured in 89% of arteries, with enhancement of soft tissue visualization. Conclusion: This study successfully evaluated an inexpensive and easy to use method to perform PMCTA for post-mortem investigations.